Sistem Informasi UMKM Bengkel Berbasis Web Menggunakan Metode SCRUM - Wahyu Adi Prabowo; Citra Wiguna (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
Strengthening on Micro, Small and Medium Enterprises (MSMEs) in Indonesia needs to be supported by the use and good information systems management. Therefore, business actors are expected to be able to use a operational strategy supported by the use of information systems. Workshop is one of the complex MSMEs with integrated warehousing and financial reporting. The problem faced at this workshop UMKM is that there is no synchronization between the existing stock of goods and the sales stock, as well as reporting both warehouse reporting and financial reporting. For this reason, this study aims to build a web-based MSME information system for tire & rims workshops. In building this system, researchers used the agile software development method, namely SCRUM. This method is used because the system can adjust to the needs of the product owner, which is always changing and fast in processing. The results of this scrum stage, namely the product log, sprint backlog, sprint and working increment of the software, can resolve all problems that occur with regard to time, scope and cost issues so that in the implementation of making this system application can reduce the system requirements gap during the sprint process. So that the system can be completed in accordance with the requirements needed by the user. By using this workshop's UMKM information system, all sales operational activities can be monitored properly and sales and financial reports can be well structured.